Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1038/s41467-022-35742-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of transcriptional changes in the immune system associated with pubertal development in a longitudinal cohort of children with asthma

Abstract: Puberty is an important developmental period marked by hormonal, metabolic and immune changes. Puberty also marks a shift in sex differences in susceptibility to asthma. Yet, little is known about the gene expression changes in immune cells that occur during pubertal development. Here we assess pubertal development and leukocyte gene expression in a longitudinal cohort of 251 children with asthma. We identify substantial gene expression changes associated with age and pubertal development. Gene expression chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 108 publications
0
4
0
Order By: Relevance
“…Cough sensitivity in children is instead influenced by airway caliber (forced expiratory volume in 1 s, FEV1) and age [37]. Recent data in children with asthma have shown that changes in gene expression differ between pre-and post-menarcheal females i.e., that there is a shift from a predominantly innate to an adaptive immunity [57]. Authors demonstrating this evidence have suggested that "gene expression changes associated with asthma and may explain sex differences in prevalence" [57].…”
Section: Other Major Differences Between Children and Adults With Res...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cough sensitivity in children is instead influenced by airway caliber (forced expiratory volume in 1 s, FEV1) and age [37]. Recent data in children with asthma have shown that changes in gene expression differ between pre-and post-menarcheal females i.e., that there is a shift from a predominantly innate to an adaptive immunity [57]. Authors demonstrating this evidence have suggested that "gene expression changes associated with asthma and may explain sex differences in prevalence" [57].…”
Section: Other Major Differences Between Children and Adults With Res...mentioning
confidence: 99%
“…Recent data in children with asthma have shown that changes in gene expression differ between pre-and post-menarcheal females i.e., that there is a shift from a predominantly innate to an adaptive immunity [57]. Authors demonstrating this evidence have suggested that "gene expression changes associated with asthma and may explain sex differences in prevalence" [57]. It is likely but remains unknown if similar changes related to cough sensitivity are also present.…”
Section: Other Major Differences Between Children and Adults With Res...mentioning
confidence: 99%
“…Of the 30 gene-PBMC cell type-trait triplets with PIP > 0.5, 25 involved a trait locus that had no confidently fine-mapped gene-tissue pair (no TGFM PIP > 0.5 in GTEx-only analysis corresponding to Figures 3-6). For the 18 representative traits, TGFM identified 12 gene-PBMC cell type pairs at PIP > 0.5 for autoimmune diseases and blood cell traits (Figure 7a) vs. 5 gene-PBMC cell type pairs at PIP > 0.5 for non-blood-related traits (Figure 7b; includes 2 gene-PBMC cell type pairs for Menarche age, which we conservatively labeled as non-blood-related even though it has been reported to be partially immune-mediated 88,89 ), increasing to 23 vs. 7 for all 45 traits; this validates the importance of gene expression in blood cell types for blood-related traits.…”
Section: Tgfm Pinpoints Disease Genes and Fine-grained Cell-types In ...mentioning
confidence: 99%
“…However, in females, changes in gene expression related to puberty demonstrate a positive correlation with asthma symptoms and an inverse correlation with pulmonary function. With a notable shift in the immune response from a predominantly innate to a more adaptive pattern in females ( Resztak et al, 2023 ).…”
Section: Adolescence Why Does Everything Change?mentioning
confidence: 99%